Tindakan Pembatasan Terhadap Transportasi Online Yang Dilakukan Oleh Sopir Angkot Di Terminal Pakusari - Febriyan Dwi Rachman; Intan Syah Fitri; Vindy Febita Mamangkey (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Angkot is one of the conventional forms of transportation that is often used by the public for mobility because the prices are affordable with a variety of routes and a lot of cargo. We can find Angkots easily in various city centers with units that are often many so they can be easily found. But at present, conventional transportation and online transportation, giving rise to many policies and also considerations from various parties involed in contributing betwen online and conventional parties. In all aspects, online transportation is far superios in all aspect, online transportation is far superior in all respects and in line with the deveplopment of the current era of globalization. So that the party that suffetrs the most is conventional transportation because with the times that continue to roll, angkot drivers need to survive and find solutions by taking rationalist actions to maintain the existence of angkot. Actions ned to be taken not only by the angkot driver as a party involed in this dynamic, but the intervention of the local goverment and also the trasportation agency is very important for the contribution of the angkot to balnce the social system in society. So that rationalist actions and also the role of local goverment are very important in supporting conventional transportations operations.